Estudio de factibilidad para la creación de una empresa procesadora y comercializadora de chocolates con sabores a fruta acidas, en la ciudad de Pereira Risaralda (2012)
On The developed project CUPID CHOCOLATES, different themes were proposed in the Business Administration program with an emphasis in International Business, and counting with the knowledge and tools to do this project in a practical way. With the development of market research, organizational, technical and financial support for determining the feasibility of the creation of this company. An analysis is made to know to what extent the project is feasible, taking into account all there is available for execution (resources, benefits, regional development, and policies among others) and also taking into consideration all elements that limit their execution as socio-economic factors, norms and others. CHOCOLATES CUPID is a company located in Pereira Risaralda. Its objective will be to process and market acidy chocolates with flavors such as: passion fruit, pineapple, lemon, tangerine, among others. Our main focus is to learn from different approaches (marketing, technical, administrative, legal, economic and financial) the ability to process and market these products, to consolidate the company's business idea. In order to fulfill the objectives proposed above, we referenced the methodology and specific techniques such as surveys, to help significantly in the study of the project mentioned above. According to the research results, we applied data processing techniques, in order to establish trends and preferences. Projections were made in the target population to introduce this innovation, in order to become a business opportunity. In this logical order, the processing of information and therefore the results are supported by the statistical tool. In this case, fundamental research, to universally validate conclusions that contribute knowledge in the field of Administration. 3 Invetigative